Does the Fetus With Klinefelter Syndrome Have a Disproportionately Long Femur Length at the Anatomy Ultrasound? [9P]. (May 2017) - Navathe, Reshama; Orzechowski, Kelly; Brent, Elyssa; Patel, Shivani; Ross, Judith; Weiner, Stuart
Abstract : INTRODUCTION: To determine if children with a known diagnosis of Klinefelter Syndrome (KS) had a fetal anatomy ultrasound demonstrating long femur length (FL). METHODS: Case series of males with Klinefelter Syndrome (KS) receiving medical care in the pediatric endocrinology division at Thomas Jefferson University Hospital (TJUH) in 2014. We invited the mothers of these male children to participate in our study. Women who agreed to participate signed a medical records release form, which was sent to the delivering obstetrician requesting prenatal and delivery records. Records were reviewed for demographics, biometric measurements from the 18-22 week anatomy ultrasound, and delivery outcomes. Primary outcome was FL (calculated percentile based on Hadlock) from the anatomy ultrasound. RESULTS: In 2014, there were 100 males with KS being cared for at TJUH. 52 women agreed to participate in the study. We received medical records on 40 of these women (77%); of these, 30 records had the anatomy ultrasound report and delivery information. Mean gestational age at the time of the anatomy ultrasound 19.71 weeks (SD ± 1.29 weeks). 41% of women had an amniocentesis and a known prenatal diagnosis of KS. Femur length percentile was computed based on gestational age at the time of the ultrasound; mean FL percentile was 51.6% (SD ± 14.7%, range 8.7%-77.6%). CONCLUSION: The phenotype of males with Klinefelter Syndrome commonly results in tall stature, with a disproportionately long femur from early childhood. However, fetal femur length does not appear to predict an increased risk for Klinefelter Syndrome at the time of anatomy ultrasound.